Surgical management of extensive hypertrophic scarring of the halluces secondary to a decade of untreated onychocryptosis: An illustrative case report - Samaras, Dean J (SAGE Open Med Case Rep, 2017)
Extensive hypertrophic scarring of the halluces secondary to chronic onychocryptosis is a rare condition, which causes significant physical and psychosocial effects. In this case, a 31-year-old male developed large lesions on both great toes after he delayed treatment of chronic hallucal onychocryptosis for over a decade. Current treatment options for hypertrophic and keloid lesions in the foot and ankle vary considerably and differentiation is critical for appropriate treatment planning. In this case, surgical excision with total matrixectomy (modified Zadik–Syme) was considered optimal management. Histopathology testing confirmed the diagnosis of irritated hypertrophic scar secondary to onychocryptosis. The patient was monitored closely and at 3 months post-operatively, the incisional scars exhibited progressive maturation, and there was no recurrence of the lesions and no nail regrowth. Furthermore, the halluces were only marginally shorter providing good function and cosmesis. At the long-term follow-up consultation (5.5 years), the patient indicated complete satisfaction and had returned to regular footwear and social activities. Chronic onychocryptosis can trigger and facilitate proliferation of large benign keloid-like fibrous lesions; excision with total matrixectomy can provide an excellent long-term outcome.